Information Support of Adaptive Management in Agriculture - Andrey V. ULEZ’KO; Maxim S. TRUNOV; Valerii V. REIMER (Communications of International Proceedings, 2021)
The variability of the environment for the functioning of economic entities in the agrarian sector determines the objective demand for the formation of specific mechanisms for their adaptation to the continuous transformation of economic conditions and the information support system of adaptive management. Adaptive management should be considered as a specific type of management associated with the adaptation of economic systems to changes in the environment of their functioning. The information support system of adaptive management is a set of information resources and technologies used to control the reactions of the management object to fluctuations in the operating environment and to keep it on the optimal development path. The methods and tools used to form a system of information support for adaptation management processes in agroeconomic systems can be grouped as separate blocks that implement certain functions of adaptation management. The main task of the information support system for adaptive management is to form an information fund sufficient to develop management decisions to substantiate adequate responses of the management object to changes in the functioning environment and adaptation measures associated with the optimal use of resources diverted from the production process in order to form the necessary adaptive potential.
Keywords: Information Support; Adaptive Management; Adaptation Mechanism; Adaptation Process; The Structural And Functional Approach.